2008
DOI: 10.1183/09031936.00167407
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epidermal growth factor receptor gene mutations in malignant pleural effusion of lung adenocarcinoma

Abstract: Malignant pleural effusions (MPEs) are often observed in lung cancer, especially adenocarcinoma. Epidermal growth factor receptor (EGFR) gene mutations are usually detected in lung adenocarcinoma. The purpose of the present study was to investigate the EGFR mutation rate in MPEs of lung adenocarcinoma.Between June 2005 and December 2006, 136 MPEs from lung adenocarcinoma were collected for EGFR mutation detection. In addition, between April 2001 and November 2004, 91 surgically resected specimens of lung adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
113
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 41 publications
(57 reference statements)
9
113
0
1
Order By: Relevance
“…Cytology-proven MPEs caused by lung adenocarcinoma were all included and analysed for EGFR mutations. In our previous studies on EGFR mutations, materials from 225 patients were examined [3,4].…”
Section: Patients and Tissue Procurementmentioning
confidence: 99%
See 3 more Smart Citations
“…Cytology-proven MPEs caused by lung adenocarcinoma were all included and analysed for EGFR mutations. In our previous studies on EGFR mutations, materials from 225 patients were examined [3,4].…”
Section: Patients and Tissue Procurementmentioning
confidence: 99%
“…Cancer cells in MPEs can be collected via thoracentesis, instead of through other more invasive procedures, such as biopsy or surgery [3]. Testing cancer cells for epidermal growth factor receptor (EGFR) gene (EGFR) mutation status may aid in predicting the response of EGFR-tyrosine kinase inhibitor (TKI) therapy [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the EGFR mutation rate was 70.31%, which was much higher than the above results. Wu et al (48) detected EGFR mutations in surgical resected specimens of lung adenocarcinoma. The results showed that 93 out of 136 patients with MPEs caused by lung adenocarcinoma had positive EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%